Electrochemical Behavior and Electronucleation of Copper Nanoparticles from CuCl2·H2O Using a Choline Chloride-Urea Eutectic Mixture. (19th July 2021) - Phuong, Thao Dao Vu; Phi, Thuy-Linh; Phi, Bui Huu; Van Hieu, Nguyen; Tang Nguyen, Son; Le Manh, Tu
Abstract : This work presents a thorough study on the early stage of copper electrodeposition from a choline chloride-urea deep eutectic solvent (DES). Determination of possible species in DES containing Cu 2+ ions as the electrolytes has been performed using UV-Vis measurements. Kinetic and thermodynamic aspects of copper electrodeposition on glassy carbon electrode from DES were thoroughly investigated using cyclic voltammetry (CV) and chronoamperometry (CA). Both results from CA and CV have demonstrated that the copper electrodeposition could be performed directly from DES containing a small amount of water by the single potentiostatic step technique. Theoretical approach confirmed that the direct electronucleation of copper nanoparticles in the DES can be described by a model with two contributions, namely, (i) adsorption process and (ii) a three-dimensional (3D) nucleation and diffusion-controlled growth of copper nuclei, to the total current density transients. Kinetic parameters are important for controlling morphology and chemical composition of the obtained nanoparticles, which are verified by surface characterization techniques such as SEM and EDS.